2007
DOI: 10.1111/j.1600-051x.2007.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Asepsis during periodontal surgery involving oral implants and the usefulness of peri‐operative antibiotics: a prospective, randomized, controlled clinical trial

Abstract: Antibiotics do not provide significant advantages concerning post-operative infections in case of proper asepsis. It also does not reduce peri-oral microbial contamination. It does on the other hand reduce post-operative discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 16 publications
0
110
2
2
Order By: Relevance
“…The number of assessments also varied considerably between studies, with several conducting assessments at a single time point (Abu‐Ta'a et al. , Raghoebar et al. , Gatten et al.…”
Section: Resultsmentioning
confidence: 99%
“…The number of assessments also varied considerably between studies, with several conducting assessments at a single time point (Abu‐Ta'a et al. , Raghoebar et al. , Gatten et al.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that antibiotics do not provide significant advantages concerning postoperative infections in the presence of good asepsis. 11 Most respondents (79%) placed implants using a sterile technique (gowns, masks, gloves, head covering, drapes, sterile instruments), 16% used a barrier technique as for dento-alveolar surgery and 5% operated under a surgically clean environment.…”
Section: Discussionmentioning
confidence: 99%
“…If such measures are taken, there is a very low rate of postoperative infection following periodontal surgery,[4] thereby obviating the need for using antibiotics as a prophylactic measure. However, in actual clinical practice, it has been observed that different types of antimicrobials are routinely prescribed following periodontal surgery.…”
Section: Introductionmentioning
confidence: 99%